2020
DOI: 10.3390/plants9070850
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Schistochilopsis (Hepaticae) in Pacific Asia with the Description Protochilopsis gen. nov.

Abstract: The taxonomic diversity center of Schistochilopsis is in East Asia, where the genus also shows the highest genetic diversity and morphological plasticity. The integrative survey of Schistochilopsis in East Asia was the main goal of the present account. Plant materials were obtained from recent collections made by authors in various parts of amphi-Pacific Asia; several types of specimens were also studied. The study includes phylogenetic reconstructions from nuclear ITS1,2, chloroplast trnL and trnG seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…The general topology of the trees we obtained were in agreement with those presented by Vilnet et al [ 9 ], Shaw et al [ 10 ], Bakalin et al [ 11 ], and Bakalin et al [ 8 ]. In both Bayesian phylogenetic trees ( Figure 1 and Figure 2 ), the target specimen Konstantinovia sp.…”
Section: Resultssupporting
confidence: 91%
“…The general topology of the trees we obtained were in agreement with those presented by Vilnet et al [ 9 ], Shaw et al [ 10 ], Bakalin et al [ 11 ], and Bakalin et al [ 8 ]. In both Bayesian phylogenetic trees ( Figure 1 and Figure 2 ), the target specimen Konstantinovia sp.…”
Section: Resultssupporting
confidence: 91%
“…HEPATICS Zhukova & Matveyeva, (2000), but is absent in our collections S. crassiretis -This species was reported by Zhukova & Matveyeva, (2000), but is absent in our collections S. cuspiduligera -This species was reported by Zhukova & Matveyeva, (2000), but is absent in our collections S. degenii -Rar. Zhukova & Matveyeva (2000) and found in our collection; however, molecular-pylogenetic study of the genus (Bakalin et al, 2020) showed that S. opacifolia should be considered as synonym of S. incisa. Two specimens from our collection morphologically fit to S. hyperarctica and even were tested using molecular phylogenetic data (see Bakalin et al, 2020), but also appeared mixed with morphologically heterogeneous specimens in S. incisa s.l.…”
Section: A B F E C D G Hmentioning
confidence: 53%
“…Zhukova & Matveyeva (2000) and found in our collection; however, molecular-pylogenetic study of the genus (Bakalin et al, 2020) showed that S. opacifolia should be considered as synonym of S. incisa. Two specimens from our collection morphologically fit to S. hyperarctica and even were tested using molecular phylogenetic data (see Bakalin et al, 2020), but also appeared mixed with morphologically heterogeneous specimens in S. incisa s.l. clade.…”
Section: A B F E C D G Hmentioning
confidence: 53%
“…All taxa are listed below in alphabetical order. Nomenclature follows Söderström et al (2016) , with the exception for: 1) Solenostomataceae, where the narrow genus concept was adopted; 2) acceptance of Pseudolophozia distinct from Barbilophozia ; 3) new conception of Schistochilopsis genus according to Bakalin et al (2020b) and 4) the narrow species concept in Blepharostoma (the last following Bakalin et al (2020a) ). As only a few specimens of Blepharostoma species (only in pure mats) were checked by DNA analysis, clear taxonomical status of the vast majority of Blepharostoma species found as accompanying taxa (sometimes in small amounts) to other liverworts is not known definitely.…”
Section: Resultsmentioning
confidence: 99%